Предмет: Математика,
автор: ulalaa
2целых1/7х−3целых9/11х+х =−3
Ответы
Автор ответа:
0
( 2 1/7 X ) - ( 3 9/11 X ) + X = - 3
15/7X - 42/11X + X = - 3
X * ( 15/7 - 42/11 + 1 ) = - 3
X * ( 165/77 - 294/77 + 77/77) = - 3
- 52/77 X = - 3
X = - 3 : - 52/77
X = 231/52
X = 4 23/52
15/7X - 42/11X + X = - 3
X * ( 15/7 - 42/11 + 1 ) = - 3
X * ( 165/77 - 294/77 + 77/77) = - 3
- 52/77 X = - 3
X = - 3 : - 52/77
X = 231/52
X = 4 23/52
Похожие вопросы
Предмет: Другие предметы,
автор: musakokunina
Предмет: Английский язык,
автор: 1234567869212
Предмет: Оʻzbek tili,
автор: shuhratxayitov
Предмет: География,
автор: innaklpaczkay1
Предмет: Литература,
автор: Polina040800